2007
DOI: 10.1560/ijee.53.2.129
|View full text |Cite
|
Sign up to set email alerts
|

The Domestic Cat as a Predator of Israeli Wildlife

Abstract: Predation of wildlife by domestic cats was studied in Israel. Analysis of stomach contents and data provided by observers revealed that many domestic cats enriched the diet provided by their owners with many species of wild animals, including 12 mammals, 26 birds, 18 reptiles, and one amphibian, and scavenged from garbage. The proportion of manufactured cat food and garbage dump food in the diet of urban cats decreased from 70% of stomach volume among those living in rural settlements to 44% among cats living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…There was a strong dietary overlap among seasons, habitat, and sex of cats, which is consistent with studies that demonstrate little variation in domestic urban, rural, and feral cat diet in different locations (Brickner-Braun et al 2007;Biro et al 2005;Gillies and Clout 2003). Similarly as in this study, native birds and mammals were found among the cats' kills in Great Britain (Woods et al 2003), though in urban settings, for example in Australia, these can be predominantly introduced species (Barratt 1997).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was a strong dietary overlap among seasons, habitat, and sex of cats, which is consistent with studies that demonstrate little variation in domestic urban, rural, and feral cat diet in different locations (Brickner-Braun et al 2007;Biro et al 2005;Gillies and Clout 2003). Similarly as in this study, native birds and mammals were found among the cats' kills in Great Britain (Woods et al 2003), though in urban settings, for example in Australia, these can be predominantly introduced species (Barratt 1997).…”
Section: Discussionsupporting
confidence: 89%
“…This was found to be the case in other regions of Australia (Paltridge et al 1997). Conversely in other parts of the world, invertebrate prey ranged from being insignificant on the Canary Islands (Medina and Garcia 2007) and Israeli urban areas (Brickner-Braun et al 2007) to substantial in urban and peri-urban areas of Brazil (Campos et al 2007). The insects have been suggested to play an important nutritional role in the feral cats living in xeric habitats (Medina et al 2010) (Medina et al 2010).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In most countries however (Italy is one of the exceptions: Natoli et al 1999;Natoli et al 2006), cat caretaking is not institutionalized. Free-roaming cats, moreover, are considered a problem due to their high densities, their potential to transmit zoonotic diseases, and their possible predation on wildlife (Natoli 1994;Gunther and Terkel 2002;Brickner-Braun, Geffen and Yom-Tov 2007). Consequently, caretakers often find themselves in situations in which they are forced to operate in secret because of their fear of harassment, threats, or abuse by land owners and neighbors, or demands by municipal officers to change their feeding practices.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Surveys in the United Kingdom showed that pet cats kill an estimated 85-100 million wild animals per year, of which 69% are mammals (Woods et al 2003). Another study in Israel showed that small mammals comprised 75% of the nonhuman proffered diet of domestic cats (Brickner-Braun et al 2007). Thus, domestic cats may be frequent predators of small primate species where they co-occur.…”
mentioning
confidence: 99%